Liet. eikvóti: reikšmė, daryba, etimologija - Karaliūnas, Simas (Baltistica, 1994)
LITH. eikvóti: MEANING, FORMATION AND ETYMOLOGY Lith. eikvóti (3 p. praes. -ója) and its derivative eikvótojas now have meanings „dissipate, waist, squander” and „squanderer, spendthrift, waster”. In old Lithuanian writings (e.g., M. Daukša’s Postilė and K. Sirvydas’s dictionary) they apparently had also these meanings, but not „administer, manage, run a house, a farm” and „manager, steward, housekeeper, administrator”, as is sometimes supposed. The synonyms both eiklóti (3 p. praes. -ója) and eikslúoti (3 p. praes. -úoja, praet. -ãvo) are found in dialects. This circumstance might be taken to indicate that they are denominatives, derived from respective nouns *aislas/* eiklas „mischievous, restless person, fidget, rake”, *aikslas/*eikslas „id.”, as well as и stem *аiktи/*еiktи- „id.” besides о stem *aikta- „id.’, retained in adv. aiktais „vainly“. The derivational relationship between eikvoti < *eiktvóti < *eiktu-ā- and и stem * aiktu/*eiktu- would be the same as that between nakvóti (3 p. praes. -ója) „spend, pass the night (at somebody’s place)” < *naktvoti < *naktu-ā- and и stem *noktu- „night“ (cf. Lat. посtu „at night”) against Lith. naktìs „id.“ (with a regular loss of t in the cluster -ktv-). Cognates are assumed to be, first, Lith. iš-aikštýti (3 p. praes. -aĩkšto) „make disorderly, throw about, scatter, dissipate”, an iterative of the suffix -st- (transformed into -št-after k), second, Latv. aikâties (1 p. sing, praes. -ãjuôs) „struggle and kick (of sheep when they are sheared; sometimes of children)”, aîcinât (1 p. sing, praes. -u, -ãju) „invite, ask, call”. As the meanings „pamper, spoil, coddle” and „make naughty, mischievous; get, become spoilt, naighty, dissoluted, wanton” may be related, Lith. áiklintis (3 p. praes -inasi) „pamper, indulge oneself, a derivative of * áiklas „naughty, mischievous, spoilt, wanton”, seems to belong to this group of cognate words, too. Toch. A ekär, B aikare „empty“, Toch A ekro „misarable, poor, scanty” could be seen as cognates of Lith. *áiklas „naughty, mischievous, spoit, wanton”, * aiklas/*eiklas „mischievous, restless person, fidget, rake” with regard to their formatives -r-; -l- and semantic affiliation (semasiologically cf. Lith. dỹkas „empty, hollow; naughty, mischievous, spoit”). In view of these facts a separate root *aik-/*eik- „stir, move, become restless, fidgety; cast, fling, hurl” could be reconstructed for Protobaltic. Latv. iecava „space behind an oven, space between an oven and wall; stove-pipe” and possibly „Narev Baltic" ajki „time”,if it is from *aikai „fine, hot weather”, would suggest another Protobaltic root *aik-/*eik- „burn, become heated, incandesce”.